HOW DOES FEMINISM ENGENDER THE GLOBAL PEACE AND SECURITY AGENDA? - Nhengu, Dudziro (PEOPLE: International Journal of Social Sciences, 2019)
This qualitative desk review study conceptualises the current global peace and security agenda from the standpoint of an extraordinary career path that has shifted between gender activism and political activism for peace. Women’s activism has been subjected to astute gender analysis over-time, placing women’s histography at the centre of international relations. Modern scholarship should devote attention to pre-colonial history of women’s participation in communal peace and security, developing creative methodologies for historical reconstructing, to focus on how women promulgate the peace and security agenda. Normatively, feminism has influenced a vibrant legal regime on gender equality and women’s political participation. Practically, the activism of women in Kosovo, Sierra Leone and Liberia facilitated peaceful transitions from dictatorship governments. Arguments locate women’s voices and experiences as catalysts for a past, present and future global feminist international relations discourse. The Hague Peace Conference (1915) and the Beijing Conference (1995) are cited as rallying points for women’s collective action globally to influence an alternative negotiated peace settlement, tracing links between war, nationalism, masculinity, and violence. Study concludes that the women’s movement birthed strategies to galvanize women’s collective power for a peace feminist agenda in tandem with key reference points of the UN Charter.